In situ biosynthesized gold nanoclusters inhibiting cancer development via the PI3K–AKT signaling pathway. Issue 35 (8th August 2019) - Wang, Maonan; Yu, Zeqian; Feng, Huan; Wang, Jianling; Wang, Lishan; Zhang, Yu; Yin, Lihong; Du, Ying; Jiang, Hui; Wang, Xuemei; Zhou, Jiahua
Abstract : Nanomaterials have made great breakthroughs in drug delivery. Abstract : Nanomaterials have made great breakthroughs in drug delivery. However, in previous studies, nanomaterials have been mostly used as vehicles to transport drugs into tumors. Herein, we first found that the in situ biosynthesized gold nanoparticles (Au NCs) can inhibit cancer development via the inhibition of some signaling pathways. Classical cell phenotypic assay tests and orthotropic liver tumor model both showed that the in situ biosynthesized Au NCs could inhibit tumor development. With the help of the RNA-seq analysis, we found that the in situ biosynthesized Au NCs could significantly inhibit the PI3K–AKT signaling pathway, thus effectively impeding tumor development. This facile and effective tumor targeting theranostics in vivo can effectively cure cancers in future clinical applications.